Designing and Evaluating the Usability and Onboarding for a Mixed-Reality Application: A Case Study with PEARL (Paderborn Electrical Engineering AR Laboratory) and Meta Quest 3 - Alptekin, Mesut; Münstermann, Daniel; Temmen, Katrin (Lecture Notes in Networks and Systems)
Abstract This study explores the usability and onboarding process of a Mixed Reality (MR) application called PEARL, designed to prepare students for laboratory work. Originally developed for mobile Augmented Reality (mAR), PEARL was adapted for MR to offer a more immersive and intuitive experience through hand and gesture controls. Since many students lack experience with MR devices, a user-friendly onboarding system is essential. The study aims to redesign PEARL’s user interface and onboarding experience, evaluating how intuitive interaction elements impact usability. First, a literature review will identify existing usability guidelines for MR applications, which will guide the redesign of the interface. This new version will then be tested with students through a user study. Feedback will be collected via an online survey to assess the onboarding and user experience, and the findings will be used to refine the design further. The expected outcome is an improved onboarding process and interface, making PEARL accessible even for MR novices, enhancing their ability to interact with 3D objects in a real-world setting. Ultimately, the study aims to provide best practices for developing intuitive MR interfaces and effective onboarding experiences, especially in educational contexts.
Keywords: Meta Quest 3; Augmented Reality; Mixed Reality; PEARL; Electrical Engineering; Laboratory Training; Onboarding; User Experience; User Interface; Heuristics

Evaluation of Digital Competencies - Development of an Instrument for Vocational Teacher Training - Sänger, Niklas (International Journal of Vocational Education Studies)
Approaches to modeling and evaluating teachers’ digital competencies are often based on the TPACK model. However, in-depth analyses of the conceptualization of the model show that the specificities of the so-called dual subject matter of vocational education are not sufficiently represented. This article provides insights into the development and testing of an instrument for teachers’ self-assessment of digital competencies in vocational education.The instrument is based on the structure of TPACK but is adapted in various ways to reflect the specificities of vocational education. The aim of this article is to transfer a conceptual extension oft he TPACK model into an initial instrument and to analyze it as part of an initial exploration.
Keywords: Digital Competencies; Dual Subject Matter; Evaluation; TPACK; Vocational Teacher Training

Direct parameter identification for highly nonlinear strain rate dependent constitutive models using machine learning - Gerritzen, Johannes; Hornig, Andreas; Winkler, Peter; Gude, Maik (ECCM21 - Proceedings of the 21st European Conference on Composite Materials)
Fiber reinforced plastics (FRP) exhibit strongly non-linear deformation behavior. To capture this in simulations, intricate models with a variety of parameters are typically used. The identification of values for such parameters is highly challenging and requires in depth understanding of the model itself. Machine learning (ML) is a promising approach for alleviating this challenge by directly predicting parameters based on experimental results. So far, this works mostly for purely artificial data. In this work, two approaches to generalize to experimental data are investigated: a sequential approach, leveraging understanding of the constitutive model and a direct, purely data driven approach. This is exemplary carried out for a highly non-linear strain rate dependent constitutive model for the shear behavior of FRP.The sequential model is found to work better on both artificial and experimental data. It is capable of extracting well suited parameters from the artificial data under realistic conditions. For the experimental data, the model performance depends on the composition of the experimental curves, varying between excellently suiting and reasonable predictions. Taking the expert knowledge into account for ML-model training led to far better results than the purely data driven approach. Robustifying the model predictions on experimental data promises further improvement.
Keywords: Direct parameter identification; Machine learning; Convolutional neural networks; Strain rate dependency; Fiber reinforced plastics; woven composites; segmentation; synthetic training data; x-ray computed tomography

No learning rates needed: Introducing SALSA - Stable Armijo Line Search Adaptation - Kenneweg, Philip; Kenneweg, Tristan; Fumagalli, Fabian; Hammer, Barbara (2024 International Joint Conference on Neural Networks (IJCNN))
Keywords: Training; Schedules; Codes; Search methods; Source coding; Computer architecture; Transformers

Métodos de la mediación de cultura en el entrenamiento práctico de futuros/as profesores/as de Alemán como Lengua Extranjera - Treder, Alexandra (Revista Lengua y Cultura)
This study investigates the teaching methods that future teachers of German as a foreign language use in cultural mediation. Utilizing a qualitative and hermeneutic approach, it analyzes data from a teacher-training module of the International Master's in German as a Foreign/Second Language that Friedrich Schiller University Jena in Germany offers. Participants taught an online course to students from a Japanese university, which focused on cultural learning. Within the teacher training module, the participants discussed their lesson plans, conducted classes, and subsequently reflected on their teaching practices by exploring and critiquing the practical application of their teaching skills. The analysis, which was conducted using qualitative evaluative content analysis following Kuckartz's (2018) approach, revealed a preference for distributive/instructive methods, with some recognition of interactive and collaborative methods. A tendency towards both repetitive and reflective practices was evident, with a predominant focus on content that was specific to a supposed target culture rather than intercultural or transcultural content. The study highlights the need to balance knowledge transmission with the development of critical and reflective skills in cultural mediation. It emphasizes the importance of incorporating collaborative and interactive methods, which promote a critical attitude that is necessary in language teachers and learners. In conclusion, this study advocates adaptive and reflective teaching as an essential component in the training of future language teachers in globalized contexts.
Keywords: cultural mediation; teacher training; foreign language teaching; teaching methods; teaching practice

Segment-Less Continuous Speech Separation of Meetings: Training and Evaluation Criteria - von Neumann, Thilo; Kinoshita, Keisuke; Boeddeker, Christoph; Delcroix, Marc; Haeb-Umbach, Reinhold (IEEE/ACM Transactions on Audio, Speech, and Language Processing)
Continuous Speech Separation (CSS) has been proposed to address speech overlaps during the analysis of realistic meeting-like conversations by eliminating any overlaps before further processing. CSS separates a recording of arbitrarily many speakers into a small number of overlap-free output channels, where each output channel may contain speech of multiple speakers. This is often done by applying a conventional separation model trained with Utterance-level Permutation Invariant Training (uPIT), which exclusively maps a speaker to an output channel, in sliding window approach called stitching. Recently, we introduced an alternative training scheme called Graph-PIT that teaches the separation network to directly produce output streams in the required format without stitching. It can handle an arbitrary number of speakers as long as never more of them overlap at the same time than the separator has output channels. In this contribution, we further investigate the Graph-PIT training scheme. We show in extended experiments that models trained with Graph-PIT also work in challenging reverberant conditions. Models trained in this way are able to perform segment-less CSS, i.e., without stitching, and achieve comparable and often better separation quality than the conventional CSS with uPIT and stitching. We simplify the training schedule for Graph-PIT with the recently proposed Source Aggregated Signal-to-Distortion Ratio (SA-SDR) loss. It eliminates unfavorable properties of the previously used A-SDR loss and thus enables training with Graph-PIT from scratch. Graph-PIT training relaxes the constraints w.r.t. the allowed numbers of speakers and speaking patterns which allows using a larger variety of training data. Furthermore, we introduce novel signal-level evaluation metrics for meeting scenarios, namely the source-aggregated scale- and convolution-invariant Signal-to-Distortion Ratio (SA-SI-SDR and SA-CI-SDR), which are generalizations of the commonly used SDR-based metrics for the CSS case.
Keywords: Continuous Speech Separation; Source Separation; Graph-PIT; Dynamic Programming; Permutation Invariant Training

Creating Synthetic Training Datasets for Inspection in Machine Vision Quality Gates in Manufacturing - Gräßler, Iris; Hieb, Michael (Lectures)
Manufacturing companies face the challenge of reaching required quality standards. Using optical sensors and deep learning might help. However, training deep learning algorithms require large amounts of visual training data. Using domain randomization to generate synthetic image data can alleviate this bottleneck. This paper presents the application of synthetic image training data for optical quality inspections using visual sensor technology. The results show synthetically generated training data are appropriate for visual quality inspections.
Keywords: synthetic training data; machine vision quality gates; deep learning; automated inspection and quality control; production control

Supporting Young Immigrants in Their Transition From School to Work? A Staff Perspective on Challenges of Vocational Integration Classes - Goller, Michael (International Journal for Research in Vocational Education and Training)
Context: The implementation of successful measures to support immigrants' integration in cultural, social, and economic life can be considered as one of today's greatest challenges for many societies. This is especially true for adolescent immigrants who have not yet been able to finish education or gain qualifications relevant to joining the labour market. That is why many receiving countries have developed and implemented special programmes that aim at supporting immigrants' integration by facilitating their employability. Unfortunately, not much is known about the process of implementing these programmes or about how education systems, schools, and teachers are dealing with the new situation and target group. In this contribution, the implementation, development, and challenges of German Vocational Integration Classes (VIC), as an example of comparable programmes in the EU, are investigated to address this research gap. The paper considers the following exploratory research questions: (a) What challenges have been experienced by teachers and social workers in the implementation of VIC as well as in the integration of immigrants into the labour market in recent years? (b) How can these challenges be met in the long run and how should VIC be developed to better achieve its aims? Methods: To answer these questions, a sequential qualitative study containing questionnaire and interview elements was conducted. First, teachers and social workers involved in VIC filled in a questionnaire about their experiences and experienced challenges in implementing VIC (N = 46). Then, supplementing interviews were conducted with participants from the first sample in order to generate further insights and to contextualise the findings from the first study part (N = 14). Findings: From the respondents' answers, it appears that the VIC programme is well implemented. The results show, however, that central challenges continue to exist. This concerns, for example, legal regulations or the development of adequate curricula, but also the scope and quality of language education. In addition, problems have also been identified with regard to students' culture-specific education and their individual attitudes. These prevailing problems seem to affect schooling and educational processes. In addition, respondents report feeling left alone to deal with problems and that their experiences from their daily work in VIC and with immigrants are not sufficiently taken into account in policy and school-related decisions. Conclusions: Although VIC seems well implemented, key challenges remain in the view of the participants. It was found that teachers cannot solve many of the identified problems themselves, as they require action at the level of policy or school organisation. For staff, this can be accompanied by increased stress and demotivation. For the young immigrants, the existing challenges can have a long-term impact on school success and transition to vocational education and training. The study thus highlights the importance of targeted and holistic strategies to support immigrant integration through education.
Keywords: Immigration; Educational Policy; Employability; Mixed Methods; VET; Vocational Education and Training; Transitions From Education and Training to Employment

Das Belastungserleben von Lehramtsanwärterinnen und -anwärtern im Vorbereitungsdienst - Bruns, Marike; Caruso, Carina; Ackermann, Luisa (Berufsausbildung zwischen Hygienemaßnahmen und Lockdown(s). Folgen für die schulische und außerschulische Berufsausbildung in Schule, im Betrieb und bei Bildungsträgern)
Die Ausbildung von Lehrkräften teilt sich in Studium und Vorbereitungsdienst. Während im Studium Wissen grundgelegt wird, dient der Vorbereitungsdienst, der überwiegend in der Schule stattfindet, dem Erwerb praktischer Kompetenzen, was den Rückbezug auf theoretisch fundierte Kenntnisse und den Aufbau erfahrungsbasierten Wissens umfasst. Die Maßnahmen zur Eindämmung der Corona-Pandemie verändern nicht nur den Schulalltag, sondern haben auch Einfluss auf die Kompetenzentwicklung angehender Lehrkräfte im Vorbereitungsdienst, die ihre Berufsausbildung unter veränderten Rahmenbedingungen durchführen müssen. Die aktuellen Rahmenbedingungen können u. a. aufgrund fehlender bzw. eingeschränkter Praxiserfahrungen eine reguläre Ausbildung erschweren, was zu einem erhöhten Belastungsempfinden der angehenden Lehrkräfte beitragen kann. In diesem Beitrag wird Bezug genommen auf Daten einer explorativen Interviewstudie mit Lehramtsanwärterinnen und -anwärtern aus Nordrhein-Westfalen (N = 19), die während der Pandemie im Jahr 2020 ihren Vorbereitungsdienst absolviert haben. Es wird dabei den Fragen nachgegangen, welche Belastungsfaktoren im Zusammenhang mit der Corona-Pandemie während des Vorbereitungsdienstes auftreten können und inwieweit sich angehende Lehrkräfte während ihres Vorbereitungsdienstes vor dem Hintergrund der aktuellen Rahmenbedingungen infolge der Corona-Pandemie als belastet erleben.
Keywords: Corona-Pandemie; Lehramtsanwärter:innen; Lehrer:innenausbildung; Professionalisierung; Vorbereitungsdienst / corona pandemic; prospective teachers; teacher training; professionalization; preparatory service

Theorie-Praxis-Relationierung im Praxissemester: Die Perspektive der Mentor*innen. - Caruso, Carina; Neuweg, Georg Hans; Wagner, Michael; Harteis, Christian (Zeitschrift für Erziehungswissenschaft)
In der Mehrheit der deutschen Bundesländer ist ein Langzeitpraktikum (Praxissemester) Bestandteil der Lehramtsstudiengänge. Es zielt insbesondere darauf, Theorie und Praxis miteinander in Beziehung zu setzen. Trotz der gewichtigen Rolle, die den Mentor*innen dabei zugeschrieben wird, ist deren Perspektive noch wenig untersucht. Die empirisch auffindbaren Unterschiede in der Betreuung Studierender könnten u. a. auf unterschiedliche Vorstellungen von der Beziehung zwischen Theorie und Praxis seitens der Mentor*innen zurückzuführen sein. Diese Vorstellungen interessieren in der im Folgenden dargestellten explorativen Interviewstudie, deren Daten einer strukturierenden Inhaltsanalyse unterzogen wurden. Nachstehenden Forschungsfragen wird nachgegangen: 1) Sind die Mentor*innen auf die Aufgabe der Verknüpfung von Theorie und Praxis vorbereitet? 2) Werden in den Erzählungen der Mentor*innen zu gelingenden und misslingenden Betreuungserfahrungen Theorie-Praxis-Relationierungsfiguren sichtbar, wenn ja, welche und zeigen sich Bemühungen der Verknüpfung von Theorie und Praxis? 3) Werden in den Erzählungen der Mentor*innen zur eigenen Lerngeschichte Theorie-Praxis-Relationierungsfiguren sichtbar, wenn ja, welche und welche relative Rolle spielt das Ausbildungswissen aus Sicht der Mentor*innen für die Entwicklung ihres Könnens? 4) Welches Wissensverständnis der Mentor*innen zeigt sich in den Transkripten und welche Relevanz wird Wissen im Vergleich zu Erfahrung, Reflexion von Erfahrung und Persönlichkeit zugeschrieben? Es zeigt sich, dass die Mentor*innen das Theorie-Praxis-Verhältnis in den Gesprächen selten thematisieren, die Begriffe „Wissen“ und „Können“ synonym verwenden und der Erfahrung für die Entwicklung von Können eine höhere Relevanz beimessen als dem didaktischen und pädagogischen Ausbildungswissen.
Keywords: Lehrer*innenbildung; Mentoring; Praxissemester; Professionalisierung; Theorie-Praxis-Relationierung / Teacher training; Mentoring; Internship; Professionalization; Theory-practice-relation

How to enable pre-service teachers to design technological teaching and learning inclusively? – On the nature and consideration of basic needs in teacher training - Schröer, Franz; Tenberge, Claudia (PATT39 - PATT on the Edge Technology, Innovation and Education)
Theoretical approaches to the transformation towards an inclusive educational system in Germany mostly agree on the involvement of developmental tasks in subject related research (Hinz, 2011). The common understanding of inclusion as a process geared towards equal participation of all children (Booth, 2012) requires a reflexive questioning of established values, attitudes and practices in order to develop inclusive subject related research, teacher training and teaching and learning (Pech & Schomaker, 2013). Among other things, this results in consequences for the design of pre- service teacher training. To a large extent, teacher education is driven by the promotion of central competencies, interests and self-efficacy (Baumert & Kunter, 2011). It aims towards the development and realisation of inclusive interdisciplinary science and social studies (‘Sachunterricht’) in primary education (Moser, 2018). In conjunction with largely acknowledged constructivist approaches to teaching and learning (Möller, 2001), the development of personality, the consideration of basic needs (Deci & Ryan, 1993) and promotion of individual potentials are repeatedly fundamentally represented in subject related and pedagogical considerations (Feuser, 1989; GDSU, 2013). Therefore, the aforementioned constructivist approach is connected to several certain key paradigms for teaching and learning processes (e.g., Vygotskij, 1978; Posner et al., 1982; van de Pol et al., 2010). In this regard, the nature of primary school students’ basic needs have empirically not been sufficiently studied yet. Theoretical frameworks from motivational psychology (Deci & Ryan, 1993) do not explicitly address how individual needs differ and how the diversity of needs can be included in joint-learning, multi-perspective technology education classes. The research project the present paper is part of aims to develop a research-based concept for the professionalisation of pre-service teachers in a seminar course. Therefore, the promotion of the pre- service teachers’ interests and self-efficacy expectations have been assessed in a pre-post research design with a control group visiting another course not related to technology education and inclusion. The present paper describes and discusses first results of the project and will give an outlook on subsequent developmental tasks.
Keywords: Inclusion; basic needs; pre-service teacher training; interest; self-efficacy

Organisation der dualen Berufsausbildung zum/zur Verkäufer:in und Kaufmann:frau im Einzelhandel im Zeichen der COVID-19-Pandemie. - Sommer, Christian; Szczesny, Daniela (Berufsausbildung zwischen Hygienemaßnahmen und Lockdown(s). Folgen für die schulische und außerschulische Berufsausbildung in Schule, im Betrieb und bei Bildungsträgern.)
One of the most powerful events in the still young 21st century is certainly the outbreak of the coronavirus and the following COVID-19 pandemic. Massive economic as well as social distress caused worldwide devastation. In Germany, not only stores, factories, cultural facilities were closed, but also – for the first time in history – schools were closed nationwide. Closed working sites and vocational schools, as well as working sites, which remained open due to their systemic relevance, led to so far unknown challenges in Germany’s vocational education system. A very good example are the dual apprenticeships, such as trained retail salesman, which were only partially affected by closures. The main goal of education policy was to compensate personal communication and interaction via digital media. This article’s main aim is to reveal the strategies vocational schools have developed to overcome the challenges they had to face because of the pandemic.
Keywords: COVID-19; Digitalization; Vocational education and training; Retail

Development of Methods for Coil-Based Localization by Magnetic Fields of Miniaturized Sensor Platforms in Bioprocesses - Lange, Sven; Schröder, Dominik; Hedayat, Christian; Kuhn, Harald; Hilleringmann, Ulrich (22nd IEEE International Conference on Industrial Technology (ICIT))
In this publication important aspects for the implementation of inductive locating are explained. The miniaturized sensor platform called Sens-o-Spheres is used as an application of this locating method. The sensor platform is applied in bioreactors in order to obtain the environmental parameters, which makes a localization by magnetic fields necessary. Since the properties of magnetic fields in the localization area are very different from the wave characteristics, the principle of inductive localization is investigated in this publication and explained by using electrical equivalent circuit diagrams. Thereby, inductive localization uses the coupling or the mutual inductivities between coils, which is noticeable by an induced voltage. Therefore some properties and procedures are explained to extract the location of Sens-o-Spheres or other industrial sensor platforms from the couplings of the coils. One method calculates the location from an adapted ratio calculation and the other method uses neural networks and stochastic filters to obtain the results. In the end, these results are evaluated and compared.
Keywords: Location awareness; Coils; Couplings; Nonuniform electric fields; Magnetic separation; Neural networks; Training data

Digitalisation in Agriculture: Knowledge and Learning Requirements of German Dairy Farmers - Goller, Michael; Caruso, Carina; Harteis, Christian (International Journal for Research in Vocational Education and Training)
Purpose: This study aims at investigating how digitalisation (in the sense of industry 4.0) has changed the work of farmers and how they experience the changes from more traditional work to digitalised agriculture. It also investigates what knowledge farmers require on digitalised farms and how they acquire it. Dairy farming was used as domain of investigation since it, unlike other industries, has strongly been affected by digitalisation throughout the last years. Method: Exploratory interviews with 10 livestock farmers working on digitalised dairy farms were analysed using qualitative content analysis. A deductive and inductive coding strategy was used. Findings: Farming work has changed from more manual tasks towards symbol manipulation and data processing. Farmers must be able to use computers and other digital devices to retrieve and analyse sensor data that allow them to monitor and control the processes on their farm. For this new kind of work, farmers require elaborated mental models that link traditional farming knowledge with knowledge about digital systems, including a strong understanding of production processes underlying their farm. Learning is mostly based on instructions offered by manufacturers of the new technology as well as informal and non-formal learning modes. Even younger farmers report that digital technology was not sufficiently covered in their (vocational) degrees. In general, farmers emphasises the positive effects of digitalisation both on their working as well as private life. Conclusions: Farmers should be aware of the opportunities as well as the potential drawbacks of the digitalisation of work processes in agriculture. Providers of agricultural education (like vocational schools or training institutes) need to incorporate the knowledge and skills required to work in digitalised environments (e.g., data literacy) in their syllabi. Further studies are required to assess how digitalisation changes farming practices and what knowledge as well as skills linked to these developments are required in the future.
Keywords: Work-Based Learning; Organisational Change; Digital Competences; Qualitative Research; Digitalisation; Farming; Dairy; VET; Vocational Education and Training

Graph-PIT: Generalized Permutation Invariant Training for Continuous Separation of Arbitrary Numbers of Speakers - von Neumann, Thilo; Kinoshita, Keisuke; Boeddeker, Christoph; Delcroix, Marc; Haeb-Umbach, Reinhold (Interspeech 2021)
Automatic transcription of meetings requires handling of overlapped speech, which calls for continuous speech separation (CSS) systems. The uPIT criterion was proposed for utterance-level separation with neural networks and introduces the constraint that the total number of speakers must not exceed the number of output channels. When processing meeting-like data in a segment-wise manner, i.e., by separating overlapping segments independently and stitching adjacent segments to continuous output streams, this constraint has to be fulfilled for any segment. In this contribution, we show that this constraint can be significantly relaxed. We propose a novel graph-based PIT criterion, which casts the assignment of utterances to output channels in a graph coloring problem. It only requires that the number of concurrently active speakers must not exceed the number of output channels. As a consequence, the system can process an arbitrary number of speakers and arbitrarily long segments and thus can handle more diverse scenarios. Further, the stitching algorithm for obtaining a consistent output order in neighboring segments is of less importance and can even be eliminated completely, not the least reducing the computational effort. Experiments on meeting-style WSJ data show improvements in recognition performance over using the uPIT criterion.
Keywords: Continuous speech separation; automatic speech recognition; overlapped speech; permutation invariant training

Data Science und Big Data in der beruflichen Bildung – Konzeption und Erprobung eines Projektkurses für die Sekundarstufe II - Opel, Simone Anna; Schlichtig, Michael (Sammelband der 27. Fachtagung der BAG Berufliche Bildung)
Die Themen „Big Data“, „Künstliche Intelligenz und „Data Science“ werden seit einiger Zeit nicht nur in der breiten Öffentlichkeit kontrovers diskutiert, sondern stellen für die Ausbildung in den IT- und IT-nahen Berufen schon heute neue Herausforderungen dar, die in Zukunft durch die gesellschaftliche und technologische Weiterentwicklung hin zu einer Datengesellschaft noch größer werden. An dieser Stelle stellt sich die Frage, welche Aspekte dieses großen Themenkomplexes für Schule und Ausbildung von Wichtigkeit sind und wie diese Themen sinnstiftend und gewinnbringend in die informatische Ausbildung in verschiedenen Bildungsgängen integriert werden können. Im Rahmen des von uns im Jahr 2017 organisierten Symposiums zum Thema „Data Science“ wurden für die Bildung relevante Aspekte erörtert, wodurch als Kernelemente für den Unterricht Algorithmen der Künstlichen Intelligenz und ihre Anwendung in Industrie und Gesellschaft, Explorationen von Big Data sowie der Umgang mit eigenen Daten in sozialen Netzwerken herausgearbeitet wurden. Ziel ist, aus diesen Themenbereichen sowohl ein umfassendes Curriculum als auch Module für verschiedene Unterrichtsszenarien zu entwickeln und zu erproben. Durch diese Materialien soll es Lehrkräften aus der Informatik, Mathematik oder Technik ermöglicht werden, diese Themen auf Basis des Curriculums und der erprobten Unterrichtskonzepte selbst zu unterrichten. Hierfür wurde im Rahmen des Projekts ProDaBi (Projekt Data Science und Big Data in der Schule, https://www.prodabi.de), initiiert von der Telekom Stiftung, ein experimenteller Projektkurs entwickelt, den wir mit Schüler:innen der Sekundarstufe II an der Universität Paderborn im Schuljahr 2018/19 durchführten. Dieser Kurs enthält neben einem Modul zur Exploration von Big Data und einem weiteren Modul zum Maschinellen Lernen als Teil der Künstlichen Intelligenz auch eine Projektphase, die es in Zusammenarbeit mit lokalen Unternehmen den Schüler:innen ermöglicht, das Erlernte in ein reales Data Science-Projekt einzubringen. Aus den Erfahrungen dieses Projektkurses sowie den parallel durchgeführten Erprobungen einzelner Bausteine auch mit beruflichen Schulen werden ab dem Schuljahr 2019/20 die hierfür verwendeten Materialien weiterentwickelt und weiteren Kooperationspartnern zur Erprobung zur Verfügung gestellt. Damit wurden zum Ende des Projekts nicht nur vollständige Unterrichtsmaterialien, sondern auch ein umfassendes Curriculum entwickelt.
Keywords: Berufsbildung; vocational education; Ausbildung; training; berufliche Weiterbildung; advanced vocational education; Digitalisierung; digitalization; Unterricht; teaching; Lehrmethode; teaching method; Interdisziplinarität; interdisciplinarity; Fachdidaktik; subject didactics; Curriculum; curriculum; gewerblich-technischer Beruf; vocational/technical occupation; Fachkraft; specialist; Qualifikationsanforderungen; qualification requirements; Kompetenz; competence; Lehrerbildung; teacher training; Bundesrepublik Deutschland; Federal Republic of Germany

Anforderungen an Studienordnungen in einer digital vernetzten Welt - Caruso, Carina; Martin, Alexander (Zeitschrift für Hochschulentwicklung)
Der Beitrag widmet sich der Frage, wie lehrer*innenbildende Hochschulen der Digitalisierung auf der Ebene der Überarbeitung und Anpassung von Studienordnungen begegnen können. Ziel des interdisziplinären Vorhabens ist es, ausgehend von einer Inhaltsanalyse nordrhein-westfälischer Studienordnungen einen Kriterien- bzw. Fragenkatalog zu entwickeln, der diejenigen bildungspolitischen Vorgaben zur Verankerung digitaler Kompetenz fasst, die künftigen Akkreditierungen von Studiengängen zugrunde liegen werden und der fach- und standortübergreifend eingesetzt werden kann.
Keywords: Studienordnungen; Digitalisierung; Lehrer*innenbildung; Professionalisierung / study regulations; digitalisation; teacher training; professionalisation

Auswirkungen der Digitalisierung industrieller Arbeit auf die berufliche und allgemeine Bildung - Berisha-Gawlowski, Angelina; Caruso, Carina; Goller, Michael; Harteis, Christian (Digitalisierung am Übergang Schule Beruf Ansätze und Perspektiven in Arbeitsdomänen und beruflicher Förderung)
Digitalisierung ist derzeit ein viel diskutiertes Thema. Mit ihr werden derart tief grei- fende Veränderungen der Gesellschaft und Arbeitswelt erwartet, dass sie häufig als digitale Revolution bezeichnet wird. Gleichzeitig wirft die Auseinandersetzung mit diesen antizipierten Veränderungen viele noch unbeantwortete Fragen auf. Diese umfassen unter anderem Überlegungen hinsichtlich des Substitutionspotenzials menschlicher Arbeit durch die Digitalisierung, die Frage nach der Ausgestaltung der Rolle des Menschen in der Industrie 4.0 und schließlich Erwägungen in Bezug auf die Vorbereitung und Begleitung von Beschäftigten in der digitalen Transformation. Der vorliegende Beitrag gibt Aufschluss über die Dimensionen der Digitalisierung und die derzeit diskutierten Entwicklungslinien; er befasst sich weiterhin mit den sich daraus ergebenden Herausforderungen und Bedeutungen für die industrielle Arbeit und die Beschäftigten. Abschließend werden daraus abzuleitende Implikationen für die berufliche und allgemeine Bildung diskutiert.
Keywords: Digitalisierung; Industrie 4.0; Arbeit 4.0; berufliche Aus- und Weiterbildung; allgemeine Bildung / digitalization; industry 4.0; work 4.0; vocational education and training; general education

Project “Schule für alle” as a mentoring programme in university teacher education: Professionalization processes of student teachers in different practical university phases - Kottmann, Brigitte; Pieper, Catania (Hungarian Educational Research Journal)
In the mentoring programme project “Schule für alle” (“School for all”) at the University of Bielefeld in North Rhine-Westphalia, university students of primary or special education support a child who is in a situation of crisis for more than one year. In addition, the university students receive ongoing, systematic university support (cf. Kottmann, 2007, p. 32; Kottmann, 2014, p. 380). The accompanying research by “Schule für alle” focuses on the professionalization processes of student teachers during practical phases at universities; accordingly, control groups were included on a pro rata basis. In the pre-post design, all students completed a questionnaire (cf. Pieper, Kottmann & Miller, 2018, p. 294), the evaluation of which shows few changes in the professional perception of competence. Students of the mentoring programme also regularly reflected on their practical experience. Based on the objective hermeneutics it was discovered that the conception of the project supports the process of perceiving, acknowledging and becoming more sensitive in regard to heterogeneous realities in life (cf. Pieper & Kottmann 2019b, p. 312) and that students can consciously perceive and reflect their own normative expectations (cf. Pieper & Kottmann 2019a, p. 79). The article primarily presents the results of the pre-post survey in detail and adds insights into the qualitative evaluation processes. In the conclusion, the potential of the project and mentoring programmes in general, specifically for teacher training students, is described.
Keywords: professionalization of teacher training students; practical university phases; teacher training at universities; men-toring programmes

Teaching an Oscilloscope through Progressive Onboarding in an Augmented Reality Based Virtual Laboratory - Alptekin, Mesut; Temmen, Katrin (2019 IEEE Global Engineering Education Conference (EDUCON))
The first impression is important in many aspects of human decision-making. In mobile apps, this impression can be influenced by an onboarding process. In addition, not only the user experience (UX) can be improved via onboarding, but also the user can get a very good didactical introduction to a new topic or different functionalities of an app. Therefore, this study examines different onboarding types and develops an onboarding process into an Augmented Reality (AR) based mobile application (app) that teaches students how to use and operate electro-technical laboratory equipment. This onboarding process is then assessed by students through a subsequent questionnaire in terms of attractiveness, functionality, and novelty. The results of this field study serve to examine this first prototype for possible optimizations and to further develop the app accordingly.
Keywords: Augmented Reality; Laboratory Training; Engineering Education; Progressive Onboarding